COMPOSITIONS CONTAINING ETHYLENE-BASED POLYMERS AND CYCLOANILINE INTERPOLYMERS, AND FILMS FORMED THEREOF - Patent application
A composition of ethylene polymer and crosslinked cyclouolefin interpolymer addresses the issues of rigidity and heat seal strength in films, providing efficient dispersion and high-speed processing for industrial bags.
Patent Information
- Application Number
- JP2023108123
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2017-08-23
- Filing Date
- 2023-06-30
- Publication Date
- 2025-01-29
- Estimated Expiration
- 2038-08-22
AI Technical Summary
Existing films used for industrial bags require peeling off from the enclosed material during mixing, lack sufficient rigidity and heat seal strength, and do not maintain a balance between melting temperature and seal strength.
A composition comprising ethylene polymer and crosslinked cyclouolefin interpolymer, with specific ratios and structures, is developed to create films that do not need peeling, offering rigidity, heat seal strength, and optimal melting temperature balance.
The composition achieves films with balanced rigidity, heat seal strength, and low melting temperature, suitable for industrial bag applications, ensuring efficient dispersion and high-speed processing without gel formation.
Smart Images

Figure 0007624032000044 
Figure 0007624032000045 
Figure 0007624032000046
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application is a continuation of U.S. Provisional Patent Application No. 62 / 549,14, filed August 23, 2017. Claim the benefits of No. 7. [Background technology]
[0002] It can be used to form wraps or bags, and the enclosed material is mixed Can be used to form films that do not need to be peeled off from materials (e.g. polymer pellets). There is a need for compositions that can be used to form films that are incorporated during the mixing process and The film is sufficiently stiff and flexible for proper use in industrial scale bagging lines. and heat seal strength.
[0003] The polymer compositions and / or films are described in the following references: 2003 / 097355, WO2011 / 129869, WO2015 / 004311, WO2008 / 137285, EP1525092A1, EP3016865A1, EP 2744648A1, EP717759A1, US2006 / 005741, US201 4 / 0308466, US2014 / 0363600, US2014 / 0170742, US2014 / 0170379, US2015 / 0336652, US2015 / 028 2978, US2016 / 0303833, US2016 / 0136934, US201 6 / 0244229, US4918133, US6090888, US6984442, US7288316, US8663810, US9050243, US9452593, CN104943309A (Abstract), KR2000 / 057382A (Abstract), CA22 69672A, CA2410483C, CA2170042A1 and JP2001 / 5 However, as described above, it has good rigidity and flowability and is an encapsulating material. A film that can be used for wraps or bags that does not need to be peeled away from the enclosed material when mixing ingredients. There is a need for compositions that use the same. These needs are met by the following inventions: . Summary of the Invention
[0004] A composition comprising at least the following components: A) ethylene-based polymers, B) Polymerizing ethylene and at least one bridged cyclic olefin selected from the following: A cycloolefin interpolymer comprising: a) [ka] In structure a, R1 and R2 are each independently selected from hydrogen and an alkyl group. Structure a or b) [ka] In structure b, R3 and R4 are each independently selected from hydrogen and an alkyl group. Structure B or c) [ka] In structure c, R5 and R6 are each independently selected from hydrogen and an alkyl group. Structure c or d) [ka] In structure d, R7 and R8 are each independently selected from hydrogen and an alkyl group. Structure d, e) or any combination of a)-d), Component A is present in an amount of ≧50% by weight based on the weight of the composition, and component B is A composition comprising: A component (A) and B, wherein A is present in an amount of 5 to 12% by weight, based on the combined weight of A and B. [Brief description of the drawings]
[0005] [Figure 1] The DSC profiles of EVA, POE, and a high stiffness polymer (COC) are shown, with material transitions occurring in the range of 70°C to 100°C. [Diagram 2] 1 depicts the "V0.1 (melt viscosity) vs. COC wt%" profile of the described compositions. [Diagram 3] 1 is a bar graph depicting V0.1 values of the compositions described. [Figure 4] 1 depicts the "Ec vs. Tc (peak)" profiles of the polymers and compositions described. [Diagram 5] 1 depicts the "E1 vs. Tm" profile of the described example. [Figure 6] 1 depicts the "E2 at end of melt vs. Tc onset" profile of the described example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0006] To produce a film with an optimal balance of melt temperature, stiffness, and seal strength Such films are made of polymers such as EPDM pellets. - can be used to form wraps or bags for materials, and such films Such films have low melting temperatures and do not require peeling from the encapsulated polymer. These films are commercially available. It also has sufficient stiffness and heat seal strength for suitable use on bagging lines.
[0007] As mentioned above, a composition is provided that includes at least the following components: A) ethylene-based polymers, B) Polymerizing ethylene and at least one bridged cyclic olefin selected from the following: A cycloolefin interpolymer comprising: a) [ka] In the structure a, R1 and R2 are each independently hydrogen, an alkyl group (straight-chain or R1 and R2 are each independently selected from hydrogen and or an alkyl group having 1 to 6 carbon atoms, or hydrogen or an alkyl group having 1 to 5 carbon atoms, or hydrogen hydrogen or an alkyl group having 1 to 4 carbon atoms, or hydrogen or an alkyl group having 1 to 3 carbon atoms, is hydrogen or a C1-C2 alkyl group, or hydrogen or a methyl group, or Selected is a structure a or b) [ka] In structure b, R3 and R4 are each independently hydrogen, an alkyl group (straight-chain or R3 and R4 are each independently selected from hydrogen and or an alkyl group having 1 to 6 carbon atoms, or hydrogen or an alkyl group having 1 to 5 carbon atoms, or hydrogen hydrogen or an alkyl group having 1 to 4 carbon atoms, or hydrogen or an alkyl group having 1 to 3 carbon atoms, is hydrogen or a C1-C2 alkyl group, or hydrogen or a methyl group, or Selected, structure b or c) [ka] In structure c, R5 and R6 are each independently hydrogen, an alkyl group (straight-chain or R5 and R6 are each independently selected from hydrogen and or an alkyl group having 1 to 6 carbon atoms, or hydrogen or an alkyl group having 1 to 5 carbon atoms, or hydrogen hydrogen or an alkyl group having 1 to 4 carbon atoms, or hydrogen or an alkyl group having 1 to 3 carbon atoms, is hydrogen or a C1-C2 alkyl group, or hydrogen or a methyl group, or Selected, structure c or d) [ka] In structure d, R7 and R8 are each independently hydrogen, an alkyl group (straight chain or R7 and R8 are each independently selected from hydrogen and or an alkyl group having 1 to 6 carbon atoms, or hydrogen or an alkyl group having 1 to 5 carbon atoms, or hydrogen hydrogen or an alkyl group having 1 to 4 carbon atoms, or hydrogen or an alkyl group having 1 to 3 carbon atoms, is hydrogen or a C1-C2 alkyl group, or hydrogen or a methyl group, or Selected, structure d or e) or any combination of a)-d), Component A is present in an amount of ≧50% by weight based on the weight of the composition, and component B is A composition comprising: A component (A) and B, wherein A is present in an amount of 5 to 12% by weight, based on the combined weight of A and B.
[0008] The composition may comprise a combination of two or more embodiments described herein. Each component of the article may include a combination of two or more embodiments described herein.
[0009] In one embodiment, the cycloolefin interpolymer of component B is heated at 60° C. to 90° C. Or has a Tg of 65°C to 90°C.
[0010] In one embodiment, the ethylene-based polymer of Component A is cured at a temperature of from 70° C. to 95° C., or from 85° C. to It has a Tm of 90°C.
[0011] In one embodiment, the ethylene-based polymer of Component A has a viscosity of ≦0.900 g / cc, or 0.890g / cc, or ≦0.885g / cc, or ≦0.880g / cc(1c c=1cm 3 )
[0012] In one embodiment, the ratio of Tg of component B to Tg of component A is from -1.0 to -5.0; is -1.1 to -4.5, or -1.1 to -4.0, or -1.1 to -3.5, or -1.1 to -3.0, or -1.1 to -2.5.
[0013] In one embodiment, component B is present in an amount of 5 to 12% by weight based on the total weight of components A and B. %, or from 5 to 11 wt. %, or from 5 to 10 wt. %.
[0014] In one embodiment, component B is present in an amount of 5 to 12 wt.%, or 5 to 12 wt.%, based on the weight of the composition. 11% by weight, or in an amount of 5-10% by weight.
[0015] In one embodiment, the weight ratio of component A to component B is 4.0 to 20.0, or 5.0 to 20.0, or 5.0 to 15.0, or 7.0 to 11.0, or 8.0 to 10.0 It is.
[0016] In one embodiment, the ethylene-based polymer of Component A is an ethylene / α-olefin interpolymer. -polymer, or ethylene / α-olefin copolymer, or ethylene / C3-C8 It is an α-olefin copolymer.
[0017] In one embodiment, the ethylene-based polymer of Component A is an ethylene / α-olefin / diolefin polymer. and ethylene / propylene / diene terpolymers (EPD M). In a further embodiment, the diene is ENB.
[0018] In one embodiment, the ethylene-based polymer of Component A is ethylene-vinyl acetate (E VA) copolymer.
[0019] In one embodiment, component A is present in an amount of ≧55 wt.%, or ≧60 wt.%, based on the weight of the composition. % by weight, or ≧65% by weight, or ≧70% by weight, or ≧75% by weight, or ≧80% by weight %, or ≧85%, or ≧84% by weight. A is ≦95 wt.%, or ≦94 wt.%, or ≦93 wt.%, based on the weight of the composition. %, or ≦92% by weight, or ≦91% by weight, or ≦90% by weight.
[0020] In one embodiment, the composition comprises, based on the weight of the composition, a sum of component A and component B of > 80% by weight, or ≧85% by weight, or ≧90% by weight, or ≧95% by weight, or In one embodiment, the composition comprises 98% by weight of component A and 98% by weight of component B, based on the weight of the composition. The total of these components is ≦100% by weight, or ≦99% by weight.
[0021] In one embodiment, the composition comprises, in polymerized form, styrene, and optionally one or more other copolymers. Contains less than 1.0% by weight, or less than 0.5% by weight, of polymer containing monomer.
[0022] In one embodiment, the cycloolefin interpolymer is an ethylene / bridged cyclic olefin interpolymer. It is a copolymer.
[0023] In one embodiment, at least one bridged cyclic olefin selected from: , a) [ka] Structure a, wherein R1 and R2 are each independently hydrogen, an alkyl group (linear or In a further embodiment, R1 and R2 are selected from the group consisting of olefins, branched or cyclic. are each independently hydrogen or a C1-C6 alkyl group, and further hydrogen or is a C1-C5 alkyl group, or hydrogen, or a C1-C4 alkyl group, or hydrogen. or a C1-C3 alkyl group, or hydrogen or a C1-C2 alkyl group, or hydrogen The alkyl group is selected from a nitrogen or methyl group, or hydrogen.
[0024] In one embodiment, at least one bridged cyclic olefin selected from: , b) [ka] Structure b, wherein R3 and R4 are each independently hydrogen, an alkyl group (linear or In a further embodiment, R1 and R2 are selected from the group consisting of olefins, branched or cyclic. are each independently hydrogen or a C1-C6 alkyl group, and further hydrogen or is a C1-C5 alkyl group, or hydrogen, or a C1-C4 alkyl group, or hydrogen. or a C1-C3 alkyl group, or hydrogen or a C1-C2 alkyl group, or hydrogen The alkyl group is selected from a nitrogen or methyl group, or hydrogen.
[0025] In one embodiment, at least one bridged cyclic olefin selected from: , c) [ka] Structure c, wherein R5 and R6 are each independently hydrogen, an alkyl group (linear or In a further embodiment, R1 and R2 are selected from the group consisting of olefins, branched or cyclic. are each independently hydrogen or a C1-C6 alkyl group, and further hydrogen or is a C1-C5 alkyl group, or hydrogen, or a C1-C4 alkyl group, or hydrogen. or a C1-C3 alkyl group, or hydrogen or a C1-C2 alkyl group, or hydrogen The alkyl group is selected from a nitrogen or methyl group, or hydrogen.
[0026] In one embodiment, at least one bridged cyclic olefin selected from: , d) [ka] Structure d, wherein R7 and R8 are each independently hydrogen, an alkyl group (linear or In a further embodiment, R1 and R2 are selected from the group consisting of olefins, branched or cyclic. are each independently hydrogen or a C1-C6 alkyl group, and further hydrogen or is a C1-C5 alkyl group, or hydrogen, or a C1-C4 alkyl group, or hydrogen. or a C1-C3 alkyl group, or hydrogen or a C1-C2 alkyl group, or hydrogen The alkyl group is selected from a nitrogen or methyl group, or hydrogen.
[0027] In one embodiment, the cycloolefin interpolymer of component B is a copolymer of ethylene and the copolymer of the present invention. A polymerizable form of only one bridged cyclic olefin selected from structures a to d defined in the detailed description. Including.
[0028] In one embodiment, the composition further comprises an ethylene vinyl acetate copolymer. In yet another embodiment, the ethylene vinyl acetate copolymer is present in an amount of about 100 to about 1500 based on the weight of the composition. , present in an amount of 5 to 20% by weight.
[0029] In one embodiment, the composition comprises a coupling agent, such as an azide compound or a peroxide. Does not contain.
[0030] The composition may include one or more additional additives. Suitable additives include fillers, antioxidants, and the like. Blocking agents, UV stabilizers, flame retardants, colorants or pigments, crosslinkers, slip agents, anti-blocking agents, and In one embodiment, the composition includes, but is not limited to, is from 0.5 to 20% by weight, or from 1 to 15% by weight, or from 5 to In a further embodiment, the composition comprises one or more additional additives in an amount of 10% by weight. 0.5 to 20% by weight, or 1 to 15% by weight, or 5 to 10% by weight, based on the weight of the composition % by weight of slip and / or anti-blocking agent.
[0031] In one embodiment, the composition further comprises a thermoplastic polymer. The polymers are propylene-based polymers, ethylene-based polymers, and olefin multiblock copolymers. Suitable ethylene-based polymers include, but are not limited to, high molecular weight terpolymers. High density polyethylene (HDPE), linear low density polyethylene (LLDPE), low density polyethylene ethylene (LDPE), homogeneously branched linear ethylene / α-olefin interpolymer or copolymer Polymers, and homogeneously branched substantially linear ethylene / α-olefin interpolymers or copolymers (homogeneous branched long chain branched ethylene / α-olefin interpolymers or Copolymers).
[0032] In one embodiment, the composition has a Tm of ≧80° C., or ≧81° C., or ≧82° C. In one embodiment, the composition has a Tm of 90°C, or ≦88°C, or ≦86°C. do.
[0033] In one embodiment, the composition has a viscosity of ≧35,000 Pa·s, or ≧40,000 Pa·s. s, or a V0.1(190°C) value of ≥ 45,000 Pa s. , the composition has a viscosity of ≦65,000 Pa·s, or ≦60,000 Pa·s, or ≦55, It has a V0.1(190℃) value of 1,000 Pa·s.
[0034] In one embodiment, the composition has a viscosity of 2,800 Pa·s to 4,000 Pa·s, or 3, 000Pa·s~3,800Pa·s, or 3,200Pa·s~3,600Pa·s It has a V100(190℃) value of
[0035] In one embodiment, the composition has a V0.1 / V1 ratio of ≧10, or ≧11, or ≧12. In one embodiment, the composition has a RR value of ≦16, or ≦15, or ≦00. It has a V0.1 / V100(RR) value of 14.
[0036] In one embodiment, the composition has a viscosity of 0.84 to 0.92, or 0.85 to 0.91, or has an E1 value of 0.86 to 0.90.
[0037] In one embodiment, the composition has a viscosity of 0.92 to 0.98, or 0.93 to 0.97, or has an E2 value of 0.94 to 0.96.
[0038] In one embodiment, the composition has a viscosity of 0.40 to 0.60, or 0.41 to 0.59, or has an Ec value of 0.42 to 0.58.
[0039] Also provided herein is at least one composition formed from the composition of any one or more of the embodiments described herein. In a further embodiment, a film is provided comprising at least one layer. ≦0.5wt%, or ≦0.2wt%, or ≦0.1wt% ethylene / bridged cyclic olefin A film comprising a core layer formed from a core composition comprising a fluorine interpolymer or copolymer. In a further embodiment, the core composition is an ethylene / bridged cyclic olefin interpolymer. Does not contain polymers or copolymers.
[0040] In one embodiment, the film comprises 1 to 12 weight percent ethyl acetate based on the weight of the composition. The composition comprises a cyclic olefin / bridged cyclic olefin interpolymer or copolymer. It also includes at least one additional layer.
[0041] Also provided is a film comprising at least three layers a / b / c, where layer b has a weight average molecular weight of ≦1.0 %, or ≦0.5 wt.%, or ≦0.2 wt.%, or ≦0.1 wt.%, or zero The composition comprises a cyclic olefin / bridged cyclic olefin interpolymer or copolymer. , layer a and / or layer c may each independently be one or more of the embodiments described herein. The composition is:
[0042] Also provided is a film comprising at least five layers a / b / c / d / e, where layer c is ≦1 0.0% by weight, or ≦0.5% by weight, or ≦0.2% by weight, ≦0.1% by weight, or zero From a composition containing an ethylene / bridged cyclic olefin interpolymer or copolymer and layer a, layer b, layer d and / or layer e are each independently formed according to any of the methods described herein. The composition is formed from one or more of the embodiments.
[0043] Also provided is a film comprising at least six layers a / b / c / d / e / f, with layers c and and layer d are each independently ≦1.0 wt. %, or ≦0.5 wt. %, or ≦0.2 % by weight, ≦0.1% by weight, or zero ethylene / bridged cyclic olefin interpolymers or a copolymer, and the layer a, the layer b, the layer e and / or the layer f are Each is independently formed from the composition of one or more of the embodiments described herein.
[0044] In one embodiment, formed from the composition of any one or more of the embodiments described herein. The film containing at least one layer having a thickness of 0.5 to 10 mils, or 4 to 7 mils, or or 5 to 6 mils thick.
[0045] Also provided herein is at least one composition formed from the composition of any one or more of the embodiments described herein. An article is provided that includes a further component.
[0046] Also provided herein is a method for producing at least one embodiment of a film comprising the steps of: An article is provided that includes both components.
[0047] definition Unless otherwise indicated implicitly from the context or customary in the art, All parts and percentages are by weight and all test methods are current as of the filing date of this disclosure. It exists.
[0048] As used herein, the term "composition" refers to a material that comprises the composition, as well as a This includes reaction products and decomposition products formed from materials of any reaction or decomposition product. Decomposition products are usually present in trace or residual amounts.
[0049] As used herein, the term "polymer" refers to polymers of the same or different types. It refers to a polymeric compound prepared by polymerizing monomers, whether polymerized or unpolymerized. Therefore, the general term polymer is a homopolymer (a polymer containing trace amounts of impurities). Only one type of monomer can be incorporated into the mer structure. (used to refer to a polymer prepared from) and interpolymers defined below Trace impurities such as catalyst residues may occur within the polymer and / or It can be incorporated into a polymer.
[0050] As used herein, the term "interpolymer" refers to a polymer that is made up of at least two different polymers. It refers to a polymer prepared by polymerization of monomers of the same type. The term copolymer (prepared from two different types of monomers) is Polymers) and prepared from three or more different types of monomers The polymers include those that have been
[0051] As used herein, the term "olefin-based polymer" refers to polymers that are 50% by weight or more Half the amount of olefin monomer, e.g., ethylene or propylene (based on the weight of the polymer) (In some embodiments, the term "polymer") refers to a polymer that contains, in polymerized form, one or more comonomers, and may optionally contain one or more comonomers.
[0052] As used herein, the term "ethylene-based polymer" refers to polymers that are 50% by weight or more Refers to a polymer that contains, in polymerized form, weight percent ethylene (based on the weight of the polymer). and may optionally contain one or more comonomers.
[0053] As used herein, the term "ethylene-based interpolymer" refers to polymers having up to 50% by weight or a majority weight percent ethylene (based on the weight of the interpolymer), and "Interpolymer" refers to an interpolymer that contains at least one comonomer in polymerized form.
[0054] As used herein, the term "ethylene-based copolymer" refers to a copolymer of two monomer types. For copolymers containing only ethylene monomer, 50% by weight or a majority amount of ethylene monomer (based on the weight of the copolymer) It refers to copolymers that contain, in polymerized form, α-olefins, and copolymers that contain, in polymerized form, α-olefins.
[0055] As used herein, the term "ethylene / α-olefin copolymer" refers to two For monomer types only, 50% by weight or a majority of ethylene monomer (copolymer based on the weight of the copolymer, and a copolymer that contains, in polymerized form, an α-olefin.
[0056] As used herein, the term "propylene-based polymer" refers to a polymer that is made up of a majority amount of propylene. Refers to a polymer containing, in polymerized form, monomers (based on the weight of the polymer), optionally containing one or more The above comonomers may be included.
[0057] The terms "comprising," "including," "having" "having," and derivatives thereof, are used herein to refer to any combination of terms specifically disclosed herein. is not intended to exclude the presence of any additional ingredients, steps or procedures, whether or not For the avoidance of doubt, through the use of the word "comprising" All compositions claimed herein are, unless otherwise specified, polymeric or otherwise. and any additional additives, adjuvants, or compounds. The term "qualitative" shall not be construed as essential to the operability of any subsequent description. The term "consisting of" specifically excludes any other component, step or procedure. Exclude any ingredient, step or procedure not described or listed in.
[0058] As one of ordinary skill in the art would understand, the term "COC" refers to cyclic olefin copolymer. vinegar.
[0059] Test Method Differential Scanning Calorimetry (DSC) (Component A, Component B, Composition) Differential scanning calorimetry (DSC) is used to measure the thermal stability of polymers (e.g., ethylene-based (PE) polymers). It is used to measure the melting and crystallization behavior of the compound. The material is first melt pressed (25,000 pounds for about 10 seconds) at about 175°C into a thin film. Then, the temperature is lowered to room temperature. Polymer film samples of about 5 to 8 mg are cut with a die punch. In the case of processed films, the sample is cut, weighed, and placed in the DSC pan. The sample is punched directly into the pan. The lid is crimped onto the pan to ensure a closed atmosphere. The sample pan is then filled with nitrogen. Place in a gas-purged calibrated DSC cell and heat to a temperature of 180°C at a rate of approximately 10°C / min. The sample is held at this temperature for 3 minutes. The sample is then heated at a rate of 10°C / min. Cool to -40°C, note any evidence of crystallization, and hold isothermal at that temperature for 3 minutes. The sample is then reheated at a rate of 10° C. / min until completely melted.
[0060] Unless otherwise stated, the peak melting point (Tm) was determined from the first heating curve and was the endothermic It corresponds to the temperature of the highest peak (strength). The crystallization temperature (Tc) is the temperature of the cooling curve (peak Tc) The melting temperature is determined by the melting curve calculated from the intersection of the two lines a and b. , and a is the tangent to the point of maximum slope on the second side of the peak. , b is the extrapolation of the baseline after melting. Tg is measured from the second heating curve and the The inflection point is determined at the midpoint of the transition. Several DSC transitions are shown in Figure 1.
[0061] Tensile strength and breaking tensile energy (MD and CD) Tensile strength and tensile energy to break (MD and CD) are measured according to ASTM D882-1 0 (average of 5 film samples in each direction, each sample is 1 inch x 6 inches or 25 mm Before characterization, the samples were cooled to 5 °C at 21 °C to 25 °C. The films were preconditioned at a relative humidity of 0% ±5 for 40 hours. This will be described in the experiment section.
[0062] density The samples for which density is to be measured are prepared according to ASTM D-1928. Measurements are performed within 1 hour of forming using ASTM D-792, Method B. .
[0063] Melt Index Melt index (I2) is ASTM-D 1238, 190℃ / 2.16kg and is reported in grams dissolved per 10 minutes.
[0064] Dynamic mechanical spectroscopy (DMS) TA Instruments ARE equipped with "25 mm parallel plates" under nitrogen purge Small angle oscillatory shear (melt DMS) was performed using S. From sample placement to the start of the test The time for the irradiation was set to 5 min for all samples. The experiments were performed at frequencies ranging from 0.1 to 100 rad / s. The strain amplitude was varied from 1 to 1 based on the response of the sample. The stress response was analyzed in terms of amplitude and phase, from which the storage modulus (G The elastic modulus (G''), dynamic viscosity (η*), loss tangent, and phase angle were determined. Viscosity at 0°C V0.1 and V100 at 190°C, and rheology ratio (at 190°C V0.1 / V100; also called "RR") was recorded. Specimens for Dynamic Mechanical Spectroscopy is a compression molded disk with a diameter of 25 mm and a thickness of 3.3 mm, and is heated at 180°C for 5 minutes. Formed at a molding pressure of 10 MPa, then quenched between cooling platens (15-20°C) for 2 minutes. It was done.
[0065] experiment The following examples are illustrative of the present invention but are not intended to limit the scope of the invention. The materials are listed in the table below. Polymers are typically in ppm amounts. It is stabilized by the above stabilizers.
[0066] ELVAX(R) 460 (hereinafter "ELVAX 460") is a registered trademark of DuPont. EVA is available from 3 ) density, 2.5g / 10 min melt index (I2), and VA content of 18 wt.% (weight of EVA) (based on)
[0067] ELVAX(R) 470 (hereinafter "ELVAX 470") is a registered trademark of DuPont. It is an EVA available from Dex (I2), and has a VA content of 18% by weight (based on the weight of EVA).
[0068] AMPACET 100329 is a slip-on chuck available from AMPACET Corp. It is a drug.
[0069] AMPACET 100342 is an anti-adhesive adhesive available from AMPACET Corp. It is an inhibitor.
[0070] AMPACET 10090 is a slip available from AMPACET Corp. It is a drug.
[0071] AMPACET 100450 is an anti-adhesive adhesive available from AMPACET Corp. It is an inhibitor.
[0072] ALCUDIA® PA-539 (hereinafter referred to as "ALCUDIA 539") is EVA available from Entec Polymers, density 0.937 g / cc , a melt index (I2) of 2 g / 10 min, and a VA content of 18 wt.% (EVA (based on weight).
[0073] ALCUDIA® PA-537 (hereinafter referred to as "ALCUDIA 537") is EVA available from Entec Polymers, density 0.941 g / cc , a melt index (I2) of 0.7 g / 10 min, and a VA content (E (based on the weight of VA).
[0074] ENGAGE(TM) 8003 (hereinafter "ENGAGE 8003") is a Ethylene / octene copolymers available from Ow Chemical Company , a density of 0.885 g / cc, a melt index (I2) of 1.0 g / 10 min, and has a Tg of -46°C.
[0075] ENGAGE(TM) 8540 (hereinafter "ENGAGE 8540") is a Ethylene / octene copolymers available from Ow Chemical Company , density of 0.908 g / cc, melt index (I2) of 1.0 g / 10 min, and has a Tg of -32°C.
[0076] ENGAGE(TM) 8100 (hereinafter "ENGAGE 8100") is a Ethylene / octene copolymers available from Ow Chemical Company It has a density of 0.87 g / cc, a melt index (I2) of 1.0 g / 10 min, and and a Tg of -52°C.
[0077] NORDEL(TM) IP 4820 (hereinafter "NIP4820") is a EPDM, 0.88g / c, available from W Chemical Company It has a density of 1.0 g / 10 min, a melt index (I2) of 1.0 g / 10 min, and a Tg of -18°C. do.
[0078] AFFINITY (trademark) PF 1140G POP (hereinafter referred to as “AFFINITY 1 "140" is an ethylene glycol ester available from The Dow Chemical Company. It is a styrene / octene copolymer with a density of 0.897 g / cc and a melamine content of 1.6 g / 10 min. It has a melting index (I2), and a Tg of -33°C.
[0079] AFFINITY (trademark) 8770G1 POP (hereinafter referred to as “AFFINITY 877 0") is ethylene available from The Dow Chemical Company / octene copolymer (random), density 0.885g / cc, 1.0g / 10 It has a melt index (I2) of 20 min, and a Tg of -46°C.
[0080] VERSIFY(TM) 2200 (hereinafter "VERSIFY 2200") is a Propylene / ethylene copolymers available from The Dow Chemical Company It is a polymer with a density of 0.876 g / cc and a melting point of 2.0 g / 10 min at 230°C. It has a mass flow rate (MFR).
[0081] LDPE 132I was purchased from The Dow Chemical Company. It is a commercially available polyethylene homopolymer with a density of 0.921 g / cc and a It has a melt index (I2) of g / 10 min.
[0082] TOPAS (trademark registration) 9506F-04 (hereinafter "TOPAS 9506F-04") ) is a COC copolymer available from Topas Advanced Polymers - (ethylene and norbornene), density 1.02g / cc, 230℃ / 2.1 6cm at 6kg (ISO 1133) 3 / 10min Melt Volume Rate (MVR), Melt index of 0.9g / 10min at 190°C / 2.16kg and Tg of 63°C has.
[0083] TOPAS (trademark registration) 8007F-04 (hereinafter "TOPAS 8007F-04") ) is a COC copolymer available from Topas Advanced Polymers - (ethylene and norbornene), density 1.02g / cc, 230℃ / 2.1 12cm at 6kg (ISO 1133) 3 / 10min Melt Volume Rate (MVR) , a melt index of 1.8 g / 10 min at 190 °C / 2.16 kg, and a T Has g.
[0084] "AB" is 20% talc mixed with 80% ENGAGE 8003 by weight. Refers to QAB.
[0085] Composition characteristics Rheology To determine the melt flow properties of the polymers and polymer compositions described above, dynamic vibration Dynamic shear measurements were performed on stainless steel 25 mm diameter steel bars at a temperature of 120°C and a strain of 10%. " parallel plates, 0.1rad s -1 ~100rad s -1 Over a range of See DMS test method above. TA Instruments Distortion The test specimen was 25 mm in diameter and 3 mm in thickness using the ARES / ARES-G2 controlled rheometer. .3mm. V0.1 and V100 are 0.1rad s -1 and 10 0rad s -1 The V0.1 / V100 ratio is a measure of the shear thinning characteristics. The effect of the "COC" content on the rheology of the composition is shown in Tables 1 to 3 below. See also Figure 3. [Table 1] [Table 2] [Table 3]
[0086] Film preparation The inventive (Inv.) and comparative (Comp.) films are presented below. Table 7A- 7F and 8 show the composition of each layer of each film, and the weight percentages are for each film layer. The weight of each composition used to form each film layer is based on the total weight of each composition used to form each film layer. Each composition was mixed in a HAAKE Rheomix 3000 equipped with a roller mixing blade. The ingredients were dry mixed and then heated to 150°C. After the ingredients were added and secured with the ram, the mixing time was 5 minutes. took it.
[0087] Each 5-layer film (skin / middle / core / middle / skin) is a 5-layer inflatable film. The blown film line is made of 25mm skin extrusion machine. 75mm 5-Layer Flat with 20mm middle / core extruder Die(30 / 10 / 20 / 10 / 30). The line includes Dual Lip A ir Ring, ABS Gravimetric Feed, and Dual Sur Equipped with face winders. Blow-up ratio of 2.2 to 3.9, 9 to 27 kg / 0.8 mil to 6 mil thickness with production speed of 2.4 to 18 meters per minute and take-off of 2.4 to 18 meters per minute The line is used for slitting and splitting the film layers on the line. The film layers were slit and separated on the line by Inv This was done for all examples except F4. Slitting on the film layer line Filtering and separation was not performed on Inv.F4, but instead remained as collapsed bubbles. Table 6 below provides the processing conditions for the preparation of the multilayer (5) film.
[0088] Inv.F3 and Comp.F12 are produced on a 7-layer blown film line. The remaining films were prepared on a five-layer blown film line. lpine 7-Layer Coextrusion Blown Film Lin e was used to manufacture the Inv.F3 and Comp.F12. This line is 20 Inserts available in 0mm and 250mm, 7 with barrier type screws ~50mm 30:1 L / D Grooved Feed Extruder, 4 components for each extruder Maguire in-line mixer, ExVis (Alpine control system), automatic meter NDC gauge thickness detection system with measurement capability for speeds and film widths up to 400 fpm Equipped with a 358° vibrating nip roll capable of 60 inches and a Pillar corona device A seven-layer coextrusion die was constructed. Table 8 below shows the composition of each film layer and the composition of each seven-layer film. The film process conditions for the preparation of the films are shown. Each weight percentage represents the weight of each film layer. Based on the total weight of each composition used to form the composition. See also Table 9. Some additional film properties are shown below in Tables 10A-10C.
[0089] Tensile properties The tensile properties are determined by the modulus of elasticity of the film's composition. The higher the modulus, the higher the The higher the stress the composition can handle without significant deformation. The stresses required to deform the material by 7% and 25% in the machine direction (MD) were reported. See Table 5.
[0090] Processing time Here, the treatment time is the time required for the composition of the film to be cooled below the transition temperature of the composition. The transition temperature is the time required for the composition to recover its typical properties and thus regain its typical properties. It is known that the higher the temperature, the faster the composition. The constraint on the temperature dependence of 60°C is At higher temperatures, crystallization should already have occurred, which is preferred for the compositions of the present invention. To explain the crystallization profile above this temperature, The meter Ec is the difference above 60°C for the total enthalpy of crystallization measured by DSC. The ratio of crystallization enthalpy was defined as the ratio of crystallization enthalpy. The "Ec as a function of crystallization temperature peak (TC peak)" of the 100% 15 ... For more information, see:
[0091] A set of "18% by weight VA EVA" with a peak melting temperature of 88°C. These compositions exhibits relatively high Tc and Ec values, with more than 40% of the crystallization enthalpy occurring at 60°C. This indicates that the constraint was exceeded. If Ec is 0.4 (40%), this is acceptable. It is expected to be completed within the processing time.
[0092] Ethylene-based polymers with melting temperatures between 75°C and 95°C. Due to the increase in crystallinity, Tc and E c increases (increase in Tc and Ec). This set of samples had a 0.4 POEs that exhibit a Tm lower than 75°C will have a Tc value lower than the 60°C constraint. Yes (Ec approaches zero, i.e., ENGAGE 8100, 0.87 density, 1MI) , their processing would be excessively long.
[0093] A composition of propylene-based elastomer (PBE) containing POE. Typically, PBE is This higher modulus of elasticity allows the PBE / POE The modulus of the blend increases until it approaches that of EVA. The fraction crystallizes at temperatures much lower than the "60°C temperature constraint" and therefore the E C, making the process impractical (crystallization above 60°C is less than 40%). Ec<0.4). Only one of the PBE samples met the crystallization enthalpy of 40%. However, as shown below, this composition has an unacceptable E2 value.
[0094] A composition of POE and COC that meets the transition temperature range of 70℃~100℃. In this case, the Tm peak of the selected POE was 82°C, and the Tg of the COC was 77°C. Various levels of COC were investigated ranging from 15% to 15% by weight. As shown in the graph, These compositions have been found to maintain the crystallization behavior of POE (EC>0.4 and Tc peak >60°C).
[0095] distributed Two temperature constraints were used to optimize the dispersion of the polymeric components of the film composition: It has been found that the two temperature-dependent constraints are: 1) 85°C A target temperature below which the composition exhibits its DSC melting temperature peak (Tm) 2) a target temperature of 95° C., below which the composition is It is desirable to indicate the onset Tm. If the "onset Tm at the end of melting" is exceeded, the melting profile Once the run is over and the DSC baseline has returned, the composition is considered to have melted.
[0096] E1. Enthalpy of fusion below 85°C relative to total enthalpy of fusion measured by DSC See Figure 5. E2. Enthalpy of fusion above Tm measured by DSC The ratio of melting enthalpy between Tm and 95° C. to that between Tm and 95° C. See FIG.
[0097] Based on the above analysis, we minimized the processing time and reduced the amount of non-dispersed polymer (gel) after compounding. In order to eliminate the presence of It has been found that. Figures 4-5 show schematic diagrams of the efficiency defined here. Table 4 below shows See also and 5. [Table 4] [Table 5] [Table 6] [Table 7-1] [Table 7-2] [Table 8-1] [Table 8-2] [Table 9-1] [Table 9-2] [Table 10-1] [Table 10-2] [Table 11] [Table 12-1] [Table 12-2] [Table 13-1] [Table 13-2] [Table 14]
[0098] Result summary Intimate mixing of the polymeric components in such blends is achieved by melt or glass transformation. This correlated with the high flowability that occurs after material transitions such as tungsten oxide and tungsten oxide. It provides good flowability and high rigidity at ambient temperatures to ensure proper transport of bagged materials. A new composition has been developed that can be easily mixed at temperatures ranging from 90℃ to 150℃. The composition can be easily dispersed and has high hot tack at sealing temperatures during packaging (>100℃). is obtained.
[0099] Ethylene-based polymers and cycloolefins with overlapping transition temperatures in the range of 70-100°C. The composition containing the fin interpolymer has excellent processing properties, dispersion properties, and tensile properties. It has been found that the solubility of the solubility-containing polymer has excellent properties and can be used to form films having excellent physical properties. The compositions of the present invention have good flow properties and therefore contribute to the quality of the final film formulation. It has good mixing.
[0100] Such compositions have also been found to provide optimization of tensile properties and processing times. The treatment time is the time required for the composition to cool below its transition temperature, Thus, the typical properties of solid-like materials are restored. In the case of olefin-based polymers, The crystallinity is varied to adjust the melting behavior, tensile properties, and processing time, but the compositions of the present invention An object does not entirely depend on crystallinity to have superior physical properties. For example, ,While both tensile properties and fast processing times benefit from maximizing crystallinity, On the other hand, good dispersion and high speed mixing benefit from low crystallinity. To provide the best balance between flow and modulus, ethylene-based polymers (POE It has been found that it has an optimal balance of cycloolefin interpolymer (COC) and It is clear. [Table 15-1] [Table 15-2] [Table 16-1] [Table 16-2] [Table 17-1] [Table 17-2] [Table 18]
Claims
1. A film comprising at least five layers a / b / c / d / e, each of said layers a, b, d and e comprising a composition comprising the following components: A) ≥80 wt. % of an ethylene / α-olefin copolymer, based on the weight of the composition, having a density of 0.87 g / cc to 0.885 g / cc and a Tm of 80° C. to 95° C.; B) 9 to 12% by weight, based on the total weight of components A and B, of a cycloolefin copolymer comprising, in polymerized form, ethylene and a bridged cyclic olefin having the following structure a, in which R1 and R2 are each independently selected from the group consisting of hydrogen and an alkyl group: a) 【Chemistry 1】 C) 5 to 10 wt. % of a slip agent, an antiblock agent, or a combination thereof; is formed from The cycloolefin copolymer of component B has a Tg of 60° C. to 90° C.; the weight ratio of component A to component B is from 4.0 to 10.0, based on the weight of the composition; the composition has a ratio of crystallization enthalpy above 60° C. to the total enthalpy of crystallization measured by DSC (Ec) of 0.40, a rheology ratio (RR) of 10.0 to 16.0, a ratio of melting enthalpy below 85° C. to the total melting enthalpy measured by DSC (E1) of 0.84 to 0.92, and a ratio of melting enthalpy between Tm and 95° C. to the total melting enthalpy above Tm measured by DSC (E2) of 0.92 to 0.98; The layer c is a composition comprising the following components: D) greater than 91 wt.%, based on the weight of the composition, of an ethylene / α-olefin copolymer having a density of ≦0.885 g / cc and a Tm of from 80° C. to 95° C.; E) less than 9% by weight, based on the total weight of components A and B, of a cycloolefin copolymer comprising, in polymerized form, ethylene and a bridged cyclic olefin having the following structure a (in structure a, R1 and R2 are each independently selected from the group consisting of hydrogen and an alkyl group); a) 【Chemistry 2】 A film formed from 2. The film of claim 1 having a thickness of 5 to 6 mils.
3. A wrap or bag comprising the film described in claim 1, wherein when the wrap or bag contains an encapsulated material, the wrap or bag does not need to be peeled from the encapsulated substance during mixing of the encapsulated material.
4. A film comprising at least five layers a / b / c / d / e, The layer a is formed from an ethylene / α-olefin copolymer, The layers d and e are made of a composition comprising the following components: A) ≥80 wt. % of an ethylene / α-olefin copolymer, based on the weight of the composition, having a density of 0.87 g / cc to 0.885 g / cc and a Tm of 80° C. to 95° C.; B) 9 to 12% by weight, based on the total weight of components A and B, of a cycloolefin copolymer comprising, in polymerized form, ethylene and a bridged cyclic olefin having the following structure a, in which R1 and R2 are each independently selected from the group consisting of hydrogen and an alkyl group: a) 【Chemistry 3】 C) 5 to 10 wt. % of a slip agent, an antiblock agent, or a combination thereof; is formed from The cycloolefin copolymer of component B has a Tg of 60° C. to 90° C.; the weight ratio of component A to component B is from 4.0 to 10.0, based on the weight of the composition; the composition has a ratio of crystallization enthalpy above 60° C. to the total enthalpy of crystallization measured by DSC (Ec) of 0.40, a rheology ratio (RR) of 10.0 to 16.0, a ratio of melting enthalpy below 85° C. to the total melting enthalpy measured by DSC (E1) of 0.84 to 0.92, and a ratio of melting enthalpy between Tm and 95° C. to the total melting enthalpy above Tm measured by DSC (E2) of 0.92 to 0.98; The layers b and c are made of a composition comprising the following components: D) greater than 91 wt.%, based on the weight of the composition, of an ethylene / α-olefin copolymer having a density of ≦0.885 g / cc and a Tm of from 80° C. to 95° C.; E) less than 9% by weight, based on the total weight of components A and B, of a cycloolefin copolymer comprising, in polymerized form, ethylene and a bridged cyclic olefin having the following structure a (in structure a, R1 and R2 are each independently selected from the group consisting of hydrogen and an alkyl group); a) 【Chemistry 4】 A film formed from 5. The film of claim 4 having a thickness of 5 to 6 mils.
Citation Information
Patent Citations
Multi-layer film and bag
JP2008238532A
Olefin-based resin film
JP2008308609A
Resin composition for moisture-proof layer formation, sealant for moisture-proof layer formation and moisture-proof film
JP2014070200A
Silicone-free multilayer shrink film for high speed packaging lines
US20050214557A1
Heat-shrinkable film, multilayered heat-shrinkable film, and production processes therefor
WO2016152248A1